“Everything will be all right (?)”: Discourses on COVID-19 in the Italian linguistic landscape - Bagna, Carla; Bellinzona, Martina (Frontiers in Communication, 2023)
The study of the linguistic landscape (LL) focuses on the representations of languages on signs placed in the public space, as well as on the ways in which individuals interact with these elements. Regulatory, infrastructural, commercial, and transgressive discourses (Scollon & Scollon, 2003), among others, emerge in these spaces, overlapping, complementing or opposing each other, reflecting changes taking place and, in turn, influencing them. The Covid-19 pandemic has affected all aspects of life, including cities, neighborhoods, and spaces in general (Marshall, 2021). Against this background, the study of the LL is fundamental to better understand not only the ways in which places have changed and how people are interpreting and experiencing them (Stroud & Mpendukana, 2009; Adami et al., 2020), but also to analyze the evolution of Covid-19 discourses since the pandemic broke out. This contribution aims to investigate how and in what terms the Covid-19 pandemic has had an impact on the Italian LL, considered both in its entirety, as a single body which, regardless of local specificities, responded to and jointly reflected on the shared shock, and specifically, assuming the city of Florence as a case study. The data collected in the three main phases of the pandemic include photographs of virtual and urban LL signs and interviews, analyzed through qualitative content analysis (Mayring, 2004) with the aim of exploring citizens' perceptions and awareness of changes in the LL of their city. The results obtained offer a photograph of complex landscapes and ecologies, which are multimodal, multi-layered, and interactive, with public and private discourses that are strongly intertwined and often complementary. Furthermore, the diachronic analysis made it possible to identify on the one hand points in common of the communication strategies in the different phases, both at a commercial and regulatory level. On the other hand, strong differences emerged in the bottom-up representations, characterized in the first phase by discourses of resilience, tolerance, hope, solidarity and patriotism, and in the second and third phase by disillusionment, despair and protest.